Evaluación de la amenaza por deslizamiento en málaga, santander, aplicando la metodología de los conjuntos difusos: un tema de geología ambiental (1999)
Using geological field and photogeological data, the Los Naranjitos landslide in Malaga, Eastern Santander province, is taken as an example to develop a methodology to evaluate mass movement hazards, following fuzzy sets theory. The factors involved in the probability of reactivation and the form to evaluate and qualify them trough linguistic variables which are based on human knowledge, are briefly exposed.  The geoscientist role, in hazard assessment as a part of risk evaluation is a major parameter in making decisions by national and regional developers and land-use planners. Traditional methodologies give information on probability of hazardous events, without taking into account local geological characteristics. That deficiency is corrected by the geoscientist, applying the fuzzy sets methodology, which well focused gives good results with low uncertainty degree.  The results of the proposed case (63 % - 73 % of probability of landslide reactivation) are very important to future investigations. It is necessary to carry out careful studies and formulate similar methodologies applied to vulnerability analysis to get integral risk assessment in mass movements.